PENGGUNAAN HAK PREROGATIF PRESIDEN DALAM MEMBERIKAN GRASI KEPADA TERPIDANA KORUPSI DI INDONESIA - Yehezkiel; Hartono, Made Sugi; suastika, i nengah (Universitas Pendidikan Ganesha, 2024)
Abstract This research aims to determine the legal regulations and considerations related to the use of the President's prerogative rights in granting clemency to corruption convicts in Indonesia. The type of research used is normative legal research by examining the absence of legal norms in considering the granting of pardon. The type of research used is a statutory approach, a case approach and a conceptual approach. The sources of legal materials used in this research consist of primary legal materials, secondary legal materials and tertiary legal materials. The technique for collecting legal materials is library research. The legal material analysis technique used is a description technique which is studied qualitatively juridically. The results of the research show that: (1) Regulations related to the granting of pardon by the President to corruption convicts in Indonesia, with reference to the provisions of UUD the 1945, UU Number 22 of 2002, and UU Number 5 of 2010. (2) The basis for the President's considerations in using The prerogative right to grant clemency to corruption convicts in Indonesia, which is the basis for considerations related to humanitarian considerations and human rights (HAM), consideration of cases of corruption convicts, and limits on the President's prerogative rights as respect for Indonesian constitutional law.